The colouring of clay body with industrial waste materials/Keraminės šukės tūrinis dažymas pramonės atliekomis - Šiaučiūnas, Raimundas; Valančienė, Virginija (Journal of Civil Engineering and Management, 2001)
Different products are produced by JSC “Palemono keramika” including brick and tile using Kertupis clay. This clay contains very small amounts of iron (III) oxide and a lot of fine break-up carbonates. Therefore the colour of clay body is lightly red. Often this colour does not satisfy the customers, especially restorers. The clay body colour improved by introducing various pigments in which the colouring oxides of Fe, Cr, Mn, Co predominate. Unfortunately, these oxides are very expensive and their use increases the production costs. The aim of this work was the investigation of possibilities to apply waste materials for colouring a clay body and to study physical and mechanical properties of the clay samples coloured by waste materials. It was established that for clay mass prepared by pouring dross or dry method the best colouring effect is reached introducing ca 7% of waste water sludge of JSC “Dzūkijos vandenys”. Such amounts of colouring materials only slightly change the properties of the ceramic samples. The density decreases by ca 100 kg/m3, the general shrinkage increases by 1% and the compressive strength by 15%. When the clay mass is prepared by a plastic paste method it is recommended to use a catalyst of iron-chromium CTK-2. Before use the catalyst must be ground in wet, filtrated and dried out. The Kertupis clay can be coloured in rich red colour by adding 30% of Dukstyna clay or 3–5% of the red pigment. The brown colour of the Kertupis clay can be obtained by introducing 3–5% of the technical MnO2. Article in Lithuanian. First Published Online: 30 Jul 2012